PENGARUH DISPLAY LAYOUT DAN VARIASI PRODUK TERHADAP MINAT BELI KONSUMEN PADA RUMAH BATIK SERUNAI KOTA PEKANBARU - Wila Septi Dita; Mashur Fadli (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The purpose of this study was to determine the effect of display layout and product variation on consumer purchasing interest at Rumah Batik Serunai, Pekanbaru City. The research method used is a quantitative approach with data collection techniques in the form of questionnaires which were responded to by 77 respondents. Respondents were determined using the Accidental Sampling technique. This study uses analysis such as validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t-test, F-test and coefficient of determination test (R2). Based on the analysis that has been carried out, the results show that the display layout and product variations have a positive and significant effect on consumer purchasing interest at Rumah Batik Serunai, Pekanbaru City